Analisis Kelembagaan Kelompok Tani Hutan Nekamese Pada Kawasan Hutan Dengan Tujuan Khusus Sisimeni Sanam, Desa Ekateta, Kecamtan Fatuleu, Kabupaten Kupang, Nusa Tenggara Timur - Diana Astuti Atok; Lusia Sulo Marimpan; Roni Haposan Sipayung; Nixon Rammang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Forest areas in Indonesia are often experience pressure due to the limited economic capacity of surrounding communities, which leads to illegal forest utilization. Therefore, the social forestry program emerged as a solution, providing legal access for communities to manage forests sustainably. One of its implementations is through the forestry partnership scheme in the Special Purpose Forest Area (KHDTK) Sisimeni Sanam, which established the Nekamese Forest Farmer Group (KTH Nekamese) as a partner in managing the area. This study aims to analyze the institutional system of KTH Nekamese and identify the factors influencing its institutional development. The research uses a qualitative method with a descriptive approach, involving interviews and field observations of 25 respondents, consisting of 16 KTH members and 9 forestry officers. The results show that the institutional system of KTH Nekamese was analyzed based on main aspects: institutional management, area management, and business management, as stipulated in the Regulation of the Minister of Environment and Forestry No. 89 of 2018 concerning Guidelines for Forest Farmer Groups. These three aspects indicate that KTH Nekamese has a complete and structured institutional system, but its supported by factors such as land availability, organizational structure, and assistance from forestry extension officers. However, the institutional is not yet functioning optimally due to serveral inhibiting factors, such as low member participation, weak administrative recordkeeping, and small-scale group enterprises with limited market access.